Glo ikke så romantisk! Økolitterære former - Friis, Elisabeth; Thomsen, Torsten Bøgh (K&K - Kultur og Klasse, 2020)
The article takes its point of departure in a contemporary Scandinavian literary debate regarding the function and possible societal impact of climate-oriented poetry and prose. Against the ecocentric, anti-modernist and anti-formalist tenets dominating this debate, Friis and Thomsen want to examine how the formal aspects of literary texts might be relevant for ecocritical work. Through critical discussion of the Scandinavian debate in relation to international ecocriticism and through analysis of two contemporary Scandinavian works of literature, the authors develop the argument that ecocritical consideration of literary form does not automatically entail anthropocentric l’art pour l’art-criticism. On the contrary, literary form is one of the ways in which literature connects to the world, challenges it, and changes the possibilities of thinking about the world, humanity, and politics both at present and in the future.